A new species of the leafhopper genus Drabescus Stål (Hemiptera: Cicadellidae: Deltocephalinae) from China, with a checklist and key to species - Lu, Lin; Webb, Mick; Zhang, Yalin (Zootaxa, 2019)
A new species of the Old World leafhopper genus Drabescus Stål (Cicadellidae: Deltocephalinae: Drabescini), D. hainanensis sp. nov., is described from Hainan Province, southern China. Figures are also given for D. albofasciatus Cai & He and D. nitens Stål and a checklist and key to species of the genus from China are provided.